1964
DOI: 10.1139/m64-019
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical Studies on the Antigens of Bordetella Pertussis

Abstract: Sonic extracts of B. pertussis were fractionated by chromatography employing DEAE-cellulose. Mouse protective antigen (MPA) was absorbed to the column and was found to be eluted over a range of salt concentrations from 0.05 to 0.35 M NaCl in dilute phosphate buffer, pH 7.2. The MPA was freed from nucleic acid impurities since these remained fixed to the column and could only be eluted with salt concentrations of 0.5 to 2.0 molarity. Some impurities of protein nature passed directly through the column. The meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1965
1965
1992
1992

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…The work of Nagel (170) also shows that HSF and protective antigen are separable. These results support previous claims that HSF and protective antigen are two different substances (43,74,210,227).…”
Section: Nature Of the Histamine-sensitizing Factor (Hsf) From Bordetsupporting
confidence: 92%
“…The work of Nagel (170) also shows that HSF and protective antigen are separable. These results support previous claims that HSF and protective antigen are two different substances (43,74,210,227).…”
Section: Nature Of the Histamine-sensitizing Factor (Hsf) From Bordetsupporting
confidence: 92%
“…The pertussis component producing this effect was designated 'histaminesensitizing factor' (HSF) by M a it l a n d , C o h n and M a c d o n a l d [10] and appears to occur in phase 1 strains of B. pertussis and in no other bacterium except possibly Brucella abortus [11]. Partially purified HSF has been obtained by M u n o z and H est e k in [14], N iw a [18] and G r if f it h s and M a so n [5] but its chemical nature is not yet known. However, current evidence points to HSF being located in the bacterial cell wall [12] and containing protein in its make up [12,21,29], Some investigators [9,12,21] have suggested that HSF may be the same as the protective antigen (PA) of B.pertussis that is responsible for immunizing children against whooping cough, but there are also contrary opinions [3,17,23].…”
Section: Introductionmentioning
confidence: 99%
“…A peak of lethal toxicity exuited in fraction 3. These data demonstrate that 11SF as well as lethal activities can not bc tefer to riboso" e particle itself.…”
Section: Tween 20mentioning
confidence: 73%